Woekering en weigering Metamorfosen en identiteit in het werk van Jacq Vogelaar - Demeyer, Hans; Vitse, Sven (SEL, 2018)
Jacq Vogelaar was the most radical champion of experimental form in post-war Dutch literature. After his debut in 1965, he published a series of novels in which he progressively pushed the dismantling of the traditional narrative form. Jacq Vogelaar was not only an innovator of literary form, but also a leading and often critical voice in the public debate on Dutch literature. By showing Vogelaar's multifaceted literary activity from diverse perspectives, Woekering en weigering offers a representation of this underrated author that is refreshing and rich in nuance. It is a well-deserved tribute to a literary monument.